Study of the Planetary Boundary Layer and its influence on cloud properties - Argyrouli, Athina (Σχολή Εφαρμοσμένων Μαθηματικών και Φυσικών Επιστημών, 2016)
The main objective of this Ph.D. Thesis was to study the impact of aerosols on cloud properties under the effect of turbulence in the PBL. The current work has been triggered by the uncertainties of cloud adjustments due to their interaction with aerosols within the PBL. The impact of turbulence and aerosols' properties on cloud development was studied in the urban environment of Athens from the database of the HygrA-CD campaign which took place in May-June 2014. This Thesis is structured in eight chapters. In Chapter 1, we present the structure and the diurnal variation of the PBL. Its turbulent characteristics are certainly important for the cloud development and are identified from the energy spectrum. The kinetic energy dissipation rate, defined from the turbulent kinetic energy budget is a variable which we can retrieve from a Doppler lidar in the PBL. Moreover, methods for tracking the PBL height with the use of lidar remote sensing techniques are discussed in the same chapter. In Chapter 2, we introduce the concept of the aerosol-cloud interactions and their impact to climate change. More specifically, the relations between aerosol properties and cloud droplet activation are briefly explained and, finally, the growth mechanisms of cloud droplets' radius in warm clouds are presented. Chapter 3 deals with the remote sensing of the atmosphere and especially of aerosols. The detailed description of the NTUA lidar instrumentation (EOLE and AIAS lidars) is part of this chapter. We provide, in an analytic method, the technical characteristics of the NTUA lidar systems. Furthermore, we describe the Klett and Raman methods for deriving aerosol characteristics regarding their optical properties, based on the received lidar signals. Calibration techniques and signal processing of raw lidar data, are also provided here. In Chapter 4, aiming to describe the interaction of light with matter, we make an introduction to the electromagnetic scattering theory and how we determine aerosols' optical properties from the scattering field. In the same chapter we also present the inversion techniques based on the aerosols optical properties, to extract information for aerosols' microphysical properties. One of these inversion algorithms has been used within this Ph.D. Thesis and it is presented in Chapter 5. The LIRIC algorithm combines active and passive remote sensing data and gives as output the profile of the aerosol volume concentrations for fine and coarse-mode particles. LIRIC was applied on several case studies over Athens. The results and sensitivity tests are included in Chapter 5. The subject of Chapter 6 is the description of the research objectives of the international experimental campaign HygrA-CD. The instrumentation network involved six participants (academic institutes and research centers). The prevailing meteorological conditions over the Athens basin were studied using a cluster analysis of the air mass backtrajectories arriving over Athens. The major findings of the campaign are included in this chapter. In particular, the vertical profiles of the aerosols' optical properties (retrieved from NTUA multi-wavelength Raman lidar data) are presented and an aerosol typing scheme has been performed. The thermodynamic state of the atmosphere was explored from radio soundings and the PBL dynamics from the wind lidar data. Moreover, in Chapter 7, two methodologies which were developed during this Ph.D. Thesis are presented. First, a methodology aimed to link the aerosol number concentrations to cloud droplet number was developed. The algorithm uses synergistic data obtained from a multi-wavelength Raman lidar and a Doppler lidar and provides estimation of the CCN spectra and the cloud droplet number. Second, a methodology aimed to quantify the vertical aerosol flux in the cloud-topped PBL, was developed. The collocated measurements from a Doppler lidar and the NTUA elastic aerosol lidar were used to estimate the aerosol turbulent flux through the eddy correlation technique. Both methodologies were applied to cases from the HygrA-CD campaign and the results are presented in Chapter 7. Finally, the conclusions and perspectives for future studies are provided in Chapter 8.